2016
DOI: 10.1042/cs20160398
|View full text |Cite
|
Sign up to set email alerts
|

Localization of corin and atrial natriuretic peptide expression in human renal segments

Abstract: Atrial natriuretic peptide (ANP)-mediated natriuretic response is a well-established cardiac endocrine function. Corin is a transmembrane protease that activates ANP in the heart. Corin expression has been detected in non-cardiac tissues including the kidney. Here we examined corin, pro-ANP/ANP and natriuretic peptide receptor-A (NPR-A) expression in human renal segments. By immunostaining and in situ hybridization, we found similar corin, pro-ANP/ANP and NPR-A protein and mRNA expression in human renal segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 59 publications
(70 reference statements)
1
32
0
1
Order By: Relevance
“…It functions as a key enzyme in the natriuretic peptide system by activating atrial natriuretic peptide, a cardiac hormone that regulates salt‐water balance and blood pressure (Zhou & Wu, ). In addition to the heart, corin is also expressed in non‐cardiac tissues, such as the pregnant uterus and kidneys, where it regulates uterine vessel remodelling and sodium reabsorption, respectively (Cui et al, ; Dong et al, ; Ichiki et al, ; Kaitu'u‐Lino et al, ; Polzin et al, ). These data indicate that corin may act in a tissue‐specific manner to participate in different physiological processes.…”
Section: Introductionmentioning
confidence: 99%
“…It functions as a key enzyme in the natriuretic peptide system by activating atrial natriuretic peptide, a cardiac hormone that regulates salt‐water balance and blood pressure (Zhou & Wu, ). In addition to the heart, corin is also expressed in non‐cardiac tissues, such as the pregnant uterus and kidneys, where it regulates uterine vessel remodelling and sodium reabsorption, respectively (Cui et al, ; Dong et al, ; Ichiki et al, ; Kaitu'u‐Lino et al, ; Polzin et al, ). These data indicate that corin may act in a tissue‐specific manner to participate in different physiological processes.…”
Section: Introductionmentioning
confidence: 99%
“…ПНП, сериновая протеаза, превращающая проПНП в активный пептид, НЭП и ГЦА-рецепторы экспрессированы в клетках нефрона, особенно в проксимальных канальцах и собирательных трубках, локализованных в мозговом веществе почек. Высокая плотность ГЦА-рецепторов обнаружена в подоцитах клубочков и гломерулярных мезангиаль-ных клетках [25][26][27]. Циркулирующие НУП и образу-ющийся локально ПНП прямо ингибируют реабсорб-цию натрия в проксимальном и дистальном сегментах нефрона, ослабляя стимулирующий эффект НА и АТ II [28], и способствуют увеличению СКФ, вызывая дилатацию прегломерулярных и сужение постгломе-рулярных артериол клубочков [29].…”
Section: Discussionunclassified
“…Besides cardiomyocytes, corin has also been detected in the kidney. Corin is distributed in epithelial cells, including those of the proximal tubule, thick ascending limb, connecting tubule, and collecting duct, but not the glomerulus (12,22). The specific distribution of corin in the kidney suggests that corin may play a specific role in regulating kidney physiology.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, corin was detected in epithelial cells, with segmental expression in the proximal tubule, thick ascending limb, connecting tubule, and throughout the collecting duct (12,22). Fang et al reported that the levels of urinary corin were markedly reduced in chronic kidney diseases, and that the reduction correlated with disease severity (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation